Implementasi Bela Negara di Era Teknologi Dalam Pembelajaran Pendidikan Kewarganegaraan - Auli Ihza Ahyati; Dinie Anggraeni Dewi (Journal on Education, 2021)
State defense and national resilience is an attitude that every citizen must have. Because every citizen, especially the younger generation, is the next generation of continuity in the life of the nation and state, therefore it is necessary to be well prepared and structured to become a developed country. State defense has a very important relationship in realizing the goals of a country itself. In the 1945 Constitution, article 27 and article 30 paragraph (1), namely regarding the rights and obligations of every citizen in efforts to defend the state and efforts to defend national security. It is necessary to instill and implement an attitude of state defense, especially among the younger generation through the existence of civic education subjects. Seeing the increasingly advanced technology era, it has had several negative impacts on national resilience as well as the waning attitude of defending the state among millennials today. Therefore, seeing the problems and challenges that will be faced in the future will be more varied and complex, therefore it is necessary to have an attitude of defending the country and its implementation in direct life. This article will present the results of research on the implementation of state defense in Citizenship Education learning. This article describes state defense activities that must be implemented in any circle, whether elementary, junior high, high school, university. Furthermore, the material in this work can be used as a reference in making curricula, as well as rules and policies regarding state defense